Reproducibility of Anterior Scalene Stiffness Measurement with Shear Wave Elastography: An Inter-Examiner Reliability Study - Varol, Umut; Sánchez-Jiménez, Elena; Valera-Calero, Juan Antonio; Plaza-Manzano, Gustavo; Fernández-de-las-Peñas, César; Navarro-Santana, Marcos José; Sanchez-Jorge, Sandra; Ortega-Santiago, Ricardo (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose Although previous studies have highlighted the clinical relevance of the anterior scalene muscle (AS) in patients with neck pain or nerve compressive syndromes, evidence reporting the diagnostic accuracy of shear wave elastography (SWE) for assessing the AS stiffness properties is lacking. This study aimed to analyze the SWE inter-examiner reliability for calculating the Young’s modulus and shear wave speed of the AS muscle in asymptomatic subjects.Materials and Methods Using a linear transducer, ultrasound images of the antero-lateral neck region at the C7 level were acquired in 35 healthy volunteers by one experienced examiner and one novice examiner. After codifying the images to blind the participants’ identity, the trial, and the side, Young’s modulus and shear wave speed were obtained by an independent experienced rater in randomized order. Intra-class correlation coefficients (ICC), standard error of measurement (SEM), minimal detectable changes (MDC), and coefficient of variation (CV%) were calculated.Results The assessed AS metrics showed no side-to-side differences (p>0.05). Sex differences were found for muscle size (p=0.002), but muscle brightness and stiffness were similar (p>0.05). Inter-examiner reliability was good for determining the AS muscle stiffness (ICC = 0.881 for Young’s modulus and 0.850 for shear wave speed).Conclusion The obtained results suggest that assessing the AS stiffness properties in asymptomatic subjects is a reliable procedure. Further studies should verify the SWE capacity for discriminating healthy and clinical populations and identify potential factors contributing to the variance of measurement errors.
Keywords: Anterior scalene; Diagnostic accuracy studies; Reliability; Shear wave elastography; Ultrasound imaging